2006
DOI: 10.1160/th06-05-0250
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of activated platelets in homing of human endothelial progenitor cells to subendothelial matrix

Abstract: SummaryEndothelial progenitor cells (EPCs) mobilize from the bone marrow in response to tissue injury and participate in vascular repair. However, there is limited data about the homing mechanisms of EPCs to vascular injury sites. Recently animal experiments indicated that platelets playa role in recruitment of EPCs to injury sites. However, data on the possible interaction between platelets and EPCs within the human system are limited. We, therefore, examined in-vitro human platelet-EPC interaction under stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 13 publications
3
69
0
5
Order By: Relevance
“…These mechanisms may include shear stress-induced up-regulation of adhesion molecules of the selectin and integrin family, which have been shown to mediate EPC arrest to the endothelium, 27,28 or capture of EPCs from the bloodstream by activated platelets, which adhere to the wall of ischemically injured microvessels. 29 Circulating EPCs have been markedly increased in the bloodstream after myocardial infarction, bypass surgery, or physical training.…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms may include shear stress-induced up-regulation of adhesion molecules of the selectin and integrin family, which have been shown to mediate EPC arrest to the endothelium, 27,28 or capture of EPCs from the bloodstream by activated platelets, which adhere to the wall of ischemically injured microvessels. 29 Circulating EPCs have been markedly increased in the bloodstream after myocardial infarction, bypass surgery, or physical training.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] Furthermore, it has been shown that the interaction of platelets with EPCs influences their chemotaxis, adhesion, activation, and differentiation into mature ECs during vascular repair. 17,19,[21][22][23][24] Collectively, these studies suggest the existence of a cross talk between EPCs and platelets in the regulation of each other's function. Received January 14, 2009; accepted September 23, 2009 …”
mentioning
confidence: 85%
“…27 In this regard, CD62P has also been involved in the interaction of platelets with EPCs. 17,21,22 Although platelets promote the homing of EPCs at sites of vascular injury and favor their differentiation into ECs, the functional consequences of such interactions on platelets remain unknown. In fact, EPCs secrete many vasoactive and angiogenic factors that may modulate vascular thrombosis and hemostasis.…”
Section: Clinical Perspective On P 2239mentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of cellular mediators, tissue specific chemokines, factors and molecular determinants involved in this interactions could be useful to identify new strategies for the vascular repair and tissue regeneration in ischemic organs [159,160] . In this contest, the chemokine CXCL12 (stromal cellderived factor-1α, SDF-1α), principally produced by platelet and stored in α granules, but also released from endothelial cells, is directly involved [161] .…”
Section: New Potential Biomarkers Of Platelet Activationmentioning
confidence: 99%